Motherhood missed : stories of loss and living from women who are childless by circumstance - Tonkin, Lois (Jessica Kingsley Publishers, 2019)
Honouring women who are childless by circumstance, these first-person stories describe their emotional responses and under-discussed grief. While exploring their sense of loss, the book also presents the hopefulness and positivity of the women interviewed and the alternative routes their lives have taken.